Comparison of clinical probability-adjusted D-dimer and age-adjusted D-dimer interpretation to exclude venous thromboembolism - Lapner, Sarah Takach; Julian, Jim A.; Linkins, Lori-Ann; Bates, Shannon M.; Kearon, Clive (Thrombosis and Haemostasis, 2017)
Two new strategies for interpreting D-dimer results have been proposed: i) using a progressively higher D-dimer threshold with increasing age (age-adjusted strategy) and ii) using a D-dimer threshold in patients with low clinical probability that is twice the threshold used in patients with moderate clinical probability (clinical probability-adjusted strategy). Our objective was to compare the diagnostic accuracy of age-adjusted and clinical probability-adjusted D-dimer interpretation in patients with a low or moderate clinical probability of venous thromboembolism (VTE). We performed a retrospective analysis of clinical data and blood samples from two prospective studies. We compared the negative predictive value (NPV) for VTE, and the proportion of patients with a negative D-dimer result, using two D-dimer interpretation strategies: the age-adjusted strategy, which uses a progressively higher D-dimer threshold with increasing age over 50 years (age in years × 10 µg/L FEU); and the clinical probability-adjusted strategy which uses a D-dimer threshold of 1000 µg/L FEU in patients with low clinical probability and 500 µg/L FEU in patients with moderate clinical probability. A total of 1649 outpatients with low or moderate clinical probability for a first suspected deep vein thrombosis or pulmonary embolism were included. The NPV of both the clinical probability-adjusted strategy (99.7%) and the age-adjusted strategy (99.6%) were similar. However, the proportion of patients with a negative result was greater with the clinical probability-adjusted strategy (56.1% vs, 50.9%; difference 5.2%; 95% CI 3.5% to 6.8%). These findings suggest that clinical probability-adjusted D-dimer interpretation is a better way of interpreting D-dimer results compared to age-adjusted interpretation.
Keywords: Venous thrombosis; D-dimer; diagnosis; sensitivity and specificity; humans